2015
DOI: 10.1179/2295333715y.0000000004
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory markers and cardiometabolic diseases

Abstract: Objectives : A growing body of evidence emerges that obesity, metabolic syndrome, type 2 diabetes and cardiovascular disease are intimately related to silent chronic inflammation.Methods : A narrative review summarizing the most recent data of the literature describing the pathological implications of various inflammatory markers in the blood and several keytissues of obese patients with cardiometabolic disorders.Results : Besides high-sensitive C-reactive protein, various circulating or in situ inflammatory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 68 publications
2
35
0
5
Order By: Relevance
“…With the current knowledge, however, it remains hard to determine whether alterations in gut microbiota and/or their metabolites are cause or consequence of cardiometabolic/inflammatory diseases. Thus, while it has been confirmed that obesity, MetS, T2DM, and CVD are usually associated with chronic inflammation (176) and convincing evidence links the gut microbiome to inflammation (177179), future research should focus on whether, how and to what extent mechanisms of inflammation and beyond are indeed bidirectional between the host and the microbiome. This requires system biological approaches and “big-data” analysis combined with in depth analysis of the effect of targeted perturbations in microbiota as well as in the host.…”
Section: Future Directionsmentioning
confidence: 99%
“…With the current knowledge, however, it remains hard to determine whether alterations in gut microbiota and/or their metabolites are cause or consequence of cardiometabolic/inflammatory diseases. Thus, while it has been confirmed that obesity, MetS, T2DM, and CVD are usually associated with chronic inflammation (176) and convincing evidence links the gut microbiome to inflammation (177179), future research should focus on whether, how and to what extent mechanisms of inflammation and beyond are indeed bidirectional between the host and the microbiome. This requires system biological approaches and “big-data” analysis combined with in depth analysis of the effect of targeted perturbations in microbiota as well as in the host.…”
Section: Future Directionsmentioning
confidence: 99%
“…Such data suggest that chronic inflammation may play a causal role in the development of obesity-related comorbidities, including aspects of the metabolic syndrome and cardiovascular disease. [9][10][11][12] Addressing chronic inflammation may reduce cardiometabolic risk and prevent the development of negative health outcomes. 9,13 Binge eating disorder is also highly associated with obesity and its negative physiological consequences, such as insulin resistance and dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Addressing chronic inflammation may reduce cardiometabolic risk and prevent the development of negative health outcomes. 9,13 Binge eating disorder is also highly associated with obesity and its negative physiological consequences, such as insulin resistance and dyslipidemia. [14][15][16] Although the association between binge eating and obesity-related comorbid conditions may be, in large part, explained by the increased weight of those with binge eating, 14,17,18 some preliminary data suggest that even independent of adiposity, adults with obesity and binge eating disorder have worse metabolic and inflammatory profiles than adults with obesity, but without the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Because inflammation plays an important role in manifestation and nature evolution of diabetes and diabetes-related CV complications, inflammatory biomarkers became to use in the diagnostic assessment of diabetics suspected of CV diseases [8]. Therefore, predictive role of peak concentration of various inflammatory biomarkers in diabetics is suggested [9,10].…”
Section: Introductionmentioning
confidence: 99%